2016
DOI: 10.19082/2970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fenton Reaction on Human Serum Albumin: An In Vitro Study

Abstract: IntroductionHuman serum albumin (HSA) is a critical protein in human blood plasma, which can be highly damaged by oxidative stress. The aim of this study was to analyze modifications of this protein after oxidation using a Fenton system.MethodsIn this 2015 experiment, different ratios of Fenton reagent (Fe2+/H2O2) was incubated with one concentration of human serum albumin (1mg/ml). Hence, HSA was incubated 30 min with various combinations of a Fenton system and quantified oxidation products such as carbonyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…3A, 0 B and 0 C ) and H 2 O 2 only (Fig. 4) revealed some oxidative potential for both, although more for Fe 2ϩ , supported by a carbonylation assessment that indicated more ROS-based oxidative damage (42) in bulk enzyme extracts in T. reesei than in P. placenta (Table 1). This might reflect some potential for Fe 2ϩ to auto-oxidize in the presence of molecular oxygen, leading to the production of HO˙in the absence of H 2 O 2 (43).…”
Section: Resultsmentioning
confidence: 77%
“…3A, 0 B and 0 C ) and H 2 O 2 only (Fig. 4) revealed some oxidative potential for both, although more for Fe 2ϩ , supported by a carbonylation assessment that indicated more ROS-based oxidative damage (42) in bulk enzyme extracts in T. reesei than in P. placenta (Table 1). This might reflect some potential for Fe 2ϩ to auto-oxidize in the presence of molecular oxygen, leading to the production of HO˙in the absence of H 2 O 2 (43).…”
Section: Resultsmentioning
confidence: 77%
“…3,4 Through an in vitro experimental approach, we demonstrated that oxidation of Hb to MeHb was completely inhibited either by PRP, PPP or albumin. Considering that serum albumin is the most abundant plasma protein as well as a physiologic iron chelator and ROS scavenger, 9,10 it is conceivable that plasma albumin contributes to the anti-oxidative role of PRP. This could explain the therapeutic effect of intra-articular injection of PRP observed in patients with haemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood samples (3 mL) containing acid-citrate-dextrose (ACD) were obtained from healthy donors who provided informed written consent. Blood was centrifuged at 180 g for 10…”
Section: Preparation Of Lysed Erythrocytes Platelet-rich Plasma (Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Lys-199 is among the amino acids involved in the intramolecular forces that stabilize ligands at site I [ 17 , 29 , 31 ]. As lysine is highly susceptible to carbonylation [ 45 ], the obtained alteration in the binding capacity provoked by Tau-NBr 2 cannot exclude the involvement of the modification of this amino-acid residue. In summary, we propose that the oxidation of Trp-214 and Lys-199 might be the main oxidative alterations provoked by Tau-NBr 2 at site I of HSA.…”
Section: Discussionmentioning
confidence: 99%